PERAN GEMBALA SEBAGAI PENDIDIK DALAM PENGGEMBALAAN DI GEREJA KRISTEN SETIA INDONESIA JEMAAT ENSINGO DESA SUNGAI DANGIN KECAMATAN NOYAN KABUPATEN SANGGAU: PERAN GEMBALA SEBAGAI PENDIDIK DALAM PENGGEMBALAAN DI GEREJA KRISTEN SETIA INDONESIA JEMAAT ENSINGO DESA SUNGAI DANGIN KECAMATAN NOYAN KABUPATEN SANGGAU - Marthen Luther Mau; Felipus Nubatonis (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
Ensingo Hamlet is one of the hamlets located in Dangin Village, Noyan District. In this hamlet stands the Indonesian Faithful Christian Church which is named GKSI Ensingo Congregation. On average, the servants of God who were sent to Ensingo to be pastors of the congregation could not last long because the members of the congregation did not have the awareness to make the pastor prosper in meeting their physical needs. Another problem that is the cause is that the members of the congregation do not have awareness in fellowship or worship God, enjoy drinking alcohol, bring down fellow church members, jealousy, and other old traits that are still plaguing their lives. The research objective is to explain the role of pastors as educators in shepherding in the Indonesian Christian Church of Ensingo Congregation. To answer the problems and research objectives, the research methodology used is qualitative research methods, by applying the methods of observation, interviews, and literature. The results of the research to be achieved are that the church pastor must play a proactive role in an intense approach that begins with diligent personal prayer, so that he has love to invite all church members to come to fellowship or worship Jesus Christ in places of worship then continue to educate and preach regularly. biblical so that God's people have loyalty in fellowship with Jesus Christ.